2005
DOI: 10.1074/jbc.m501316200
|View full text |Cite
|
Sign up to set email alerts
|

JAK/STAT3 Pathway Is Involved in Survival of Neurons in Response to Insulin-like Growth Factor and Negatively Regulated by Suppressor of Cytokine Signaling-3

Abstract: Janus kinases (JAK) and signal transducers and activator of transcription (STAT) proteins are activated in response to many cytokines and growth factors and are well studied in the immune system. This study was conducted to examine the role of the JAK/STAT pathway in neurons in response to tumor necrosis factor-␣ (TNF␣) and insulin-like growth factor-1 (IGF-1), which play a major role during neurodegeneration, and to study their effect on expression of suppressors of cytokine signaling 3 (SOCS-3), belonging to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
127
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 125 publications
(134 citation statements)
references
References 42 publications
(53 reference statements)
7
127
0
Order By: Relevance
“…IGF-1 has been shown to regulate cyclins, CDK protein expression, and retinoblastoma (Rb) protein phosphorylation in breast cancer cell lines (11). Our previous studies have shown that IGF-1 was a potent survival and rescue factor for dying neurons mediated by JAK/STAT, PI3kinase as well as JNK kinase pathway (12,13). However, the specific target genes involved in IGF-1 mediated cell survival in neuronal cells are not clear.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…IGF-1 has been shown to regulate cyclins, CDK protein expression, and retinoblastoma (Rb) protein phosphorylation in breast cancer cell lines (11). Our previous studies have shown that IGF-1 was a potent survival and rescue factor for dying neurons mediated by JAK/STAT, PI3kinase as well as JNK kinase pathway (12,13). However, the specific target genes involved in IGF-1 mediated cell survival in neuronal cells are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Cortices were dissected in Neural Basal Medium supplemented with B27, glutamine, Glutamax, penstrep, and growth factors bFGF and mEGF and 5 Â 10 6 cells were seeded in T-25 flasks and were grown at 37 C in a humidified atmosphere with 5% CO 2 (Thermo Scientific) to obtain neurospheres. Neurospheres were confirmed with the appropriate neural stem cell markers (14) and IGF-1 was used at 20 ng/ml as previously described (12). The cells were serum starved overnight prior to all stimulation experiments.…”
Section: Primary Neuronal and Neurosphere Cell Culturementioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, in primary cortical neurons, the JAK/STAT pathway mediates IGF-I-dependent cell survival, and the tyrphostin AG490, a specific JAK inhibitor, abrogates the antiapoptotic effect of IGF-I. 33 The G-protein/adenylyl cyclase/PKA pathway may underlie the IGF-I-mediated antiapoptotic activity as well. It has been shown that in certain cell types, including NIH/3T3 fibroblasts, the IGF-IR is coupled with certain types of Gproteins and receptor activation leads to a biologically significant dissociation of G-protein subunits.…”
Section: Figure 7 Continuedmentioning
confidence: 99%